2013
DOI: 10.1111/ane.12173
|View full text |Cite
|
Sign up to set email alerts
|

Dependent and paranoid personality patterns in myotonic dystrophy type 1

Abstract: Almost 60% of our patients with DM1 had clinically significant personality impairment, with dependent and paranoid personality patterns being the most common. Paranoid personality may decrease QoL in these patients, which gives us new opportunities for symptomatic therapy in DM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
3
14
0
2
Order By: Relevance
“…Some authors suggested that symptoms of juvenile DM1 begin after 1 month of life and before the age of 10 years [1], [51], others indicated that juvenile DM1 is defined by onset before 16 years of age [52]. In the present and in two previous studies [25], [53], we defined juvenile DM1 cases those subjects with symptom onset before the age of 20 years, since such a cut-off is often used for dividing juvenile and adult forms in different neurological disorders, for instance in parkinsonism. In 2000, the International Myotonic Dystrophy Consortium [54] suggested that the age at onset and disease severity of DM1 significantly correlate with the number of CGT repeats.…”
Section: Discussionsupporting
confidence: 51%
“…Some authors suggested that symptoms of juvenile DM1 begin after 1 month of life and before the age of 10 years [1], [51], others indicated that juvenile DM1 is defined by onset before 16 years of age [52]. In the present and in two previous studies [25], [53], we defined juvenile DM1 cases those subjects with symptom onset before the age of 20 years, since such a cut-off is often used for dividing juvenile and adult forms in different neurological disorders, for instance in parkinsonism. In 2000, the International Myotonic Dystrophy Consortium [54] suggested that the age at onset and disease severity of DM1 significantly correlate with the number of CGT repeats.…”
Section: Discussionsupporting
confidence: 51%
“…Although mean scores were globally in the average range for both DM1groups, results altogether suggest that patients with adult‐onset DM1 tend to show lower self‐esteem and more delusional ideation than patients with mild phenotype, which cause them to feel more anxiety and exhibit avoidant behaviors in front of novel and/or specific situations, withdrawing from communities. This phobic, avoidant, and schizotypal personality profile is in agreement with previous reports . However, these results should be interpreted with appropriate caution as they are based on self‐assessment measures rather than on a comprehensive psychological evaluation.…”
Section: Discussionsupporting
confidence: 91%
“…An important finding of the present study is that psychological traits differed across phenotypes, with the most severe phenotype tending to show more severe psychological symptoms. Previous reports , but not all , were not able to find such a link between disease severity and psychological traits. This may be attributable to various factors such as the lack of statistical power due to small sample sizes and different study designs (namely, rejection of mild DM1 phenotypes), age ranges, and ascertainment methods.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations